TO THE ISSUE OF DETERMINATION OF THE INSURABLE RESERVE VOLUME - N. V. Andrianov; O. V. Shchukina (Литьë и металлургия)
The theoretical and practical aspects of logistic function in the process of purchases are examined. The methodical recommendations for determination of the insurable reserve volume are given. The practical efficiency of optimization of the insurable reserve volume is shown.